Alterations in Cyclic AMP Metabolism in Human Bronchial Asthma. III. LEUKOCYTE AND LYMPHOCYTE RESPONSES TO STEROIDS - Parker, Charles W. (1973)
On the basis of serial studies the responsiveness of leukocytes and lymphocytes from asthmatic donors to catecholamines was increased during high dose corticosteroid therapy. Similar changes were observed in the cells of normal control subjects given 200 mg of hydrocortisone intravenously. The increase in responsiveness did not appear to be due to changes in lymphocyte subpopulations although this may be a contributing factor. In an effort to elucidate the basis for the improved response, in vitro effects of glucocorticoids on lymphocyte cyclic AMP concentrations were investigated. Glucocorticoids (prednisolone succinate, hydrocortisone, hydrocortisone phosphate, and hydrocortisone succinate) stimulated cyclic AMP accumulation in asthma and normal control lymphocytes, increases occurring within the first 2 min of incubation. In the absence of theophylline, responses were regularly obtained at 10 μM hydrocortisone and usually at 1 μM hydrocortisone but not at submicromolar steroid concentrations. Theophylline potentiated the cyclic AMP response to glucocorticoids and also increased the percentage of positive responses in the 0.01-1.0 μM corticosteroid range. Combinations of 1 μM hydrocortisone and 1 μM epinephrine were sometimes additive or synergistic but in many instances higher glucocorticoid concentrations were needed to obtain augmentation of the catecholamine response. The in vitro glucocorticoid effects may not fully explain their potentiating action in vivo.